CT-guided mapping in the removal of an impalpable, radiopaque foreign body in subcutaneous tissue: a case report. (2nd July 2020) - Omori, Naoko; Ueda, Takuya; Mitsukawa, Nobuyuki
Abstract : Small fragments sometimes penetrate the soft tissue, and their depth and location can be difficult to determine accurately. This case study describes localisation of a thin, short wire that had penetrated the soft tissue of a 24-year-old man's back, using computed tomography (CT) with a reference grid made with an angiographic catheter. The axial non-contrast-enhanced CT scan with the grid placed over the affected body part surveyed by the CT scout view showed that the foreign body was buried in fascia 7cm from a puncture wound. Surgical removal of the foreign body was then performed without any sequelae. CT with the use of external references that do not cause metal artefacts is a simple and helpful procedure in localising radiopaque foreign bodies.